Forms of Agricultural Organization in the Islamic Maghreb from the fourth century AH to the seventh century AH 10-13AD - khelfat, Kamel (The Algerian Historical Journal, 2026)
The historical and geographicalblogs recorded the nature of the economic relations thatprevailed in the Islamic Maghreb in the Middle Ages; This article reflects the mostprominent agricultural organizationscarried out by the Islamic Maghreb countries from the fourthcentury to the seventhcentury AH / 10-13 AD in order to advance the pace of trade exchangesbetween the various commercial centerswithin the external and internalmarkets; And how political and economicfactorscontrolled agricultural organizationsacross the stages of countries. Humanfactorsalsocontrolled the agricultural organization in the Islamic Maghreb and thusreflectedthat on the trade relations between countries in the studiedperiodfrom 4-7 AH/10-13 AD; And the extent of the state’spreservation of the agricultural organizationthatprevailedunder the political and military conditions.